(untitled) (Revista Contexto & Saúde, 2026)
Objective: To estimate the prevalence and factors associated with gestational syphilis. Methodology: A cross-sectional study was carried out in two maternity hospitals of a municipality of Rio Grande do Sul, including 2,292 new mothers from January 1 to December 31, 2019, with analysis adjusted by means of Poisson regression, using a hierarchical three-level model. contemplating demographic, socioeconomic, reproductive and gestational variables. Results: A prevalence of gestational syphilis of 5.8% (n=132) was observed. In the adjusted analysis, the occurrence of syphilis during pregnancy showed a statistically significant association with maternal age (p 0.001; 95%CI: 1.10-2.99), living with a partner (p 0.001; 95%CI: 1.50-3.14) and maternal schooling (p 0.001; 95%CI: 2.01-11.46). Conclusion: The study identified a high occurrence of syphilis in pregnancy in the municipality, influenced by sociodemographic factors, especially maternal age, absence of partner and low education. These findings highlight the need for public health strategies aimed at reducing social inequalities, strengthening prenatal care and expanding access to diagnosis and treatment, aiming at the prevention of gestational syphilis.